TEKNIK TERAPI KELOMPOK (GROUP THERAPHY) - Sitti Trinurmi (240-540X)
Group therapy is used when patients experience characteristics of disorders such as self-concept confusion, low self-esteem, changes in sensory perception, hallucinations, violence, or withdrawal from the social environment that can no longer be handled by individual therapy. In practice, group therapy varies as much as individual therapy. The earliest forms of group therapy were didactic in which the group leader lectured, reassured, and directed. Due to new developments in this field, group leaders perform the same functions for groups as individual therapists do for their patients. He encourages, reveals, examines motives, provides interpretations, and gradually evokes the participation of each member of the group in this function. Uses of Group Therapy. Participation in a group therapy experience will remove the patient's feelings of isolation and uniqueness from his illness, thereby dispelling his anxieties and encouraging him to talk about his inner feelings wholeheartedly.